Upaya Meningkatkan Hasil Belajar Siswa dengan Menggunakan Peta Konsep dalam Pembelajaran Seni Tari di Kelas X MIPA 3 SMA N 2 Padang Panjang - Widari Yolanda Putri; Yensharti Yensharti (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This study aims to describe the use of Concept Mapping and the application of concept maps in improving students' mastery of dance learning at SMA N 2 Padang Panjang. The type of research is Classroom Action Research (PTK) concept mapping method which is carried out in 2 cycles. This research instrument is in the form of observation sheets and practice tests. Data were collected through literature studies, observations, interviews, standardized tests and documentation. The data was analyzed using the percentage formula. The results of the study show that the use of the concept mapping method can improve students' thinking skills in learning cultural arts (dance), namely the concept and variety of Minangkabau traditional dances at SMA N 2 Padang Panjang. Students' abilities increase because they are given actions and are given repeated exercises in the learning process. The use of the concept map method in learning dance art is able to trigger students' enthusiasm and activeness in learning process activities. This can be seen from the increase in student learning activities from each meeting and from the test results of each cycle. The results obtained in the first cycle the average class obtained was 58.8% with poor criteria, at the end of the second cycle, the average class also increased where the results obtained were 70.3%, with good criteria. The increase from cycle I to cycle II was 11.5%.